Intensification of Downslope Nutrient Transport and Associated Biological Responses Over the Northeastern South China Sea During Wind-Driven Downwelling: A Modeling Study - Han, Aiqin; Gan, Jianping; Dai, Minhan; Lu, Zhongming; Liang, Linlin; Zhao, Xiaozheng (Frontiers in Marine Science, 2021)
Coastal downwelling is generally considered to have a limited biological effect compared with coastal upwelling. In this study, downslope transport of nearshore, nutrient-enriched waters during downwelling is found to induce distinct biological productivity in the water column over the northeastern South China Sea (NSCS). By conducting a process-driven study over a widened shelf with intensified downwelling in the NSCS, we investigated the biophysical processes associated with strong nutrient enrichment in the water column of downwelled waters. These processes and underlying mechanisms are largely unreported and remain unclear. Field measurements and a three-dimensional coupled physical-biological model incorporating nitrate (N), phytoplankton (P), zooplankton (Z), and detritus (D) were utilized to investigate distinct cross-shore nutrient transport over the uniquely widened NSCS shelf. We revealed that intensified downwelling circulation, dynamically induced by the widened shelf topography, enhanced chlorophyll a and biological productivity in a strip of well-mixed water over the inner shelf as well as in the downwelled water over the mid-shelf. Strong time lags and spatial differences existed among N, P, and Z because of the physical transport and the ensuing biogeochemical response. The intensified downslope transport of nutrient-rich coastal water formed distinct cross-shore wedge-shaped P, Z, and D structures, while N was rapidly consumed in the water column. This study illustrates the underlying coupled physical-biogeochemical processes associated with the observed biogeochemical response to wind-driven downwelling circulation over the variable shelf, which are commonly found in coastal oceans worldwide.